Influence of Bed Preparation on the Incorporation of Autogenous Bone Grafts: A Study in Dogs - De Carvalho, Paulo Sérgio Perri; Vasconcellos, Laércio Wonrath; Pi, Joan (My University, 2000)
To study the influence of bed preparation on the incorporation of autogenous bone grafts in mandibles, 6 dogs with 3 different types of receptor bed were used: cortical, perforated, and decorticated. After 45 and 90 days, the animals were sacrificed and block sections of grafted and adjacent bone were removed. The specimens were prepared and stained with hematoxylin and eosin and Masson's trichromic. The autogenous bone grafts were integrated with the receptor bed, mainly in the perforated and decorticated groups. The poorest results were found in the cortical group.
Keywords: Alveolar ridge augmentation; Bone transplantation